Het beschavingsoffensief van de Hogere Burgerschool - Blokker, Jan (Studium, 2018)
The HBS (Higher Burger School), set up by the law of 2 May 1863, intended to civilize the upper middle class. Its curriculum devoted much time to ‘modern’ subjects, particularly the natural sciences. The legislator aspired to establish the new educational system into the most remote corners of the country. In liberal circles, the view prevailed that the Netherlands had fallen behind the neighbouring countries in terms of general development. They considered their educational reforms part of a program of general rejuvenation of society. The success of the program relied on the enthusiastic cooperation of local drivers, eager to give their own community a prominent place in a progressive, civilized world. Establishment of a modern school, the Higher Civil School, was for many liberal-inspired local authorities therefore a very desirable purpose.